The translocated c-myc oncogene of Raji Burkitt lymphoma cells is not expressed in human lymphoblastoid cells. - Nishikura, K (1985)
We hybridized Raji Burkitt lymphoma cells, which carry a t(8;14) chromosome translocation, with human lymphoblastoid cells to study the expression of the translocated cellular myc oncogene (c-myc) in the hybrid cells. In Raji cells the c-myc oncogene is translocated to a switch region of the gamma heavy chain locus (S gamma). Because of sequence alterations in the 5' exon of the translocated c-myc oncogene in this cell line, it is possible to distinguish the transcripts of the translocated c-myc gene and of the normal c-myc gene. S1 nuclease protection experiments with a c-myc first exon probe indicate that Raji cells express predominantly the translocated c-myc gene, while the level of expression of the normal c-myc gene is less than 2% of that of the translocated c-myc gene. Somatic cell hybrids between Raji and human lymphoblastoid cells retain the lymphoblastoid phenotype and express only the normal c-myc oncogene. This result indicates that the activation of a c-myc oncogene translocated to a S region depends on the stage of B-cell differentiation of the cells harboring the translocated c-myc gene and not on alterations in the structure of the translocated c-myc oncogene.